Analisis Penyebab Turunnya Kinerja Kompresor untuk Tindakan Perawatan pada Kapal Tanker MT. Sea Serenity - Putra, Afrionaldi; Mukhnizar, Mukhnizar; Abu, Risal; Zulkarnain, Zulkarnain; Azman, Azmil (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Compressor is one of the equipment on the ship in the process of smooth sailing for the purposes of starting the main engine and also functions to increase gas pressure, distribute air to other parts so that the process runs smoothly. MT Tanker Ship. Sea Serenity is a goods delivery ship. On this ship, the compressor is used to carry out maneuvers, namely the main air compressor which produces air pressure of 12 bar for 10 minutes, but it should only be 5 minutes, meaning the compressor performance is not optimal. The causes of decreased performance in the compressor are: Dirty/clogged air valve, wear of the piston ring/housing, non-functioning of the low pressure and high pressure suction valves. Recommendations for maintenance activities on the LSHC-50A air compressor are: Ensure air circulation to the compressor room is clean/free from dust or dirt, add an air filter, and maintain room temperature stability (providing air conditioning). Maintain the cleanliness of the blower, check the oil filter, replace damaged pistons, and replace new piston rings according to compressor spare parts every 6000 working hours